Management practices in maritime affairs: insights from STIP Jakarta graduates - Larsen Barasa; Marudut Bernadtua Simanjuntak (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
This research investigates management practices in Marketing, Innovation, and Technology within Maritime Affairs, focusing on graduates from the Maritime Institute Jakarta (STIP Jakarta). Against the backdrop of a dynamic and competitive maritime industry, this study aims to shed light on the current landscape of management practices and their impact on operational efficiency and competitiveness. Through qualitative analysis of 70 officers' perspectives, including deck and engine officers and shipping professionals, key insights emerge. The study highlights the significance of digital marketing, continuous improvement, and technology adoption in enhancing competitiveness and operational efficiency within the maritime industry. Additionally, emphasis is placed on professionalism and adherence to international standards such as the IMO-STCW, underscoring the industry's commitment to safety, competency, and regulatory compliance. The findings underscore the interconnectedness of effective management practices, regulatory compliance, and professional development, offering actionable insights for industry practitioners, policymakers, and training institutions to navigate the complexities of maritime management effectively. The research employs a qualitative approach, utilizing interviews and thematic analysis to capture nuanced perspectives from industry professionals. Through purposive sampling, 70 officers, including deck and engine officers and shipping professionals, were selected for in-depth interviews. The data collection process involved semi-structured interviews, allowing for a comprehensive exploration of participants' experiences and insights. Thematic analysis was employed to identify patterns and themes within the data, providing a rich and detailed understanding of the key issues at hand. This research contributes to the existing literature by providing a detailed examination of management practices in Marketing, Innovation, and Technology within Maritime Affairs, offering practical implications for industry stakeholders and training institutions.